Category of Fuzzy Sets - Prasad, Bidyanand (Academic Voices: A Multidisciplinary Journal, 2011)
In the present paper, the concept of category theory, the category of fuzzy sets and the theory of flou sets are introduced. This article also shows the isomorphism between the category of fuzzy sets and flou sets. Keywords Category, flou sets, fuzzy sets, morphism, functor DOI: http://dx.doi.org/10.3126/av.v1i0.5301 Academic Voices 2011; 1: 13-15